Metagenomic analysis of bacterial communities and antibiotic resistance genes in the Eriocheir sinensis freshwater aquaculture environment. (June 2019) - Fang, Hao; Huang, Kailong; Yu, Junnan; Ding, Chengcheng; Wang, Zhifeng; Zhao, Cheng; Yuan, Hezhong; Wang, Zhuang; Wang, Se; Hu, Jianlin; Cui, Yibin
Abstract: Aquaculture has attracted significant attention as an environmental gateway to the development of antibiotic resistance. The industry of Chinese mitten crab Eriocheir sinensis contributes significantly to the freshwater aquaculture industry in China. However, the situation of antibiotic resistance in the E. sinensis aquaculture environment is not known. In this study, high-throughput sequencing based metagenomic approaches were used to comprehensively investigate the structure of bacterial communities, the abundance and diversity of antibiotic resistance genes (ARGs), as well as mobile genetic elements (MGEs) in three E. sinensis aquaculture ponds in Jiangsu Province, China. The dominant phyla were Proteobacteria, Actinobacteria, and Bacteroidetes in water samples and Proteobacteria, Chloroflexi, Verrucomicrobia, and Bacteroidetes in sediment samples. Bacitracin and multidrug were predominant ARG types in water and sediment samples, respectively. There was a significant correlation between MGEs and ARGs. In particular, plasmids were the most abundant MGEs and strongly correlated with ARGs. This is the first study of antibiotic resistome that uses metagenomic approaches in the E. sinensis aquaculture environment. The results indicate that the opportunistic pathogens may acquire ARGs via horizontal gene transfer, intensifying the potential risk to human health. Highlights: Proteobacteria was dominant in Eriocheir sinensis freshwater aquaculture. Bacitracin and multidrug were predominant ARGs in water and sediment samples. MGEs were significantly correlated to ARGs. Plasmids were the most abundant MGEs in three Chinese mitten crab ponds.